Teaching multimedia Echinotherapy as means of reference for the treatment of patients with cerebral paralysis - Juliet Rodríguez Santana; Hery Leyva González; Jorge de Lázaro Coll Costa (Centro Provincial de Información de Ciencias Médicas, 2022)
Introduction: Echinotherapy is used in Cuba as a variant of the physical-motor treatment of patients with cerebral paralysis since 1997. There have been several resources that have been used since the beginnings to reach the way in the logical development of this process. The present work is about a digital means that provides the necessary tools for the adaptation of the professionals work dedicated to this activity and that specifically intervene in the treatment of patients in children age.  Objective: To evaluate the impact of the teaching multimedia Echinotherapy as means of reference for the treatment of patients with cerebral paralysis.  Method: A qualitative study of 53 professionals, belonging to the ministries of Education, Public Health and INDER of Havana, was carried out from January, 2018 to March, 2019. The proposal was applied and evaluated in 3 fundamental phases, for which the questionnaire and  observation guide were used.   Results: Pedagogic and functional aspects were remarkable. Among the first ones some indicators were notable, such as adaptation to the teaching context, promotion of initiative and self-learning (with 5 points each one), preservation of the users service (4.8 points), as well as diversity of contents and activities (4.7 points); among the seconds, the efficient indicator prevailed for its purpose with 4.8 points. Also, the possibilities of application and incidence in the acquisition of developed contents were recognized.  Conclusion: The obtained results offer reliability and security in the product, as well as they show a positive incidence in the postdegree education, which will benefit professionals and patients  who will receive this service.